SOCIOLINGUISTIC CHARACTERISTICS OF DIALECT-SPECIFIC WORDS IN ENGLISH AND UZBEK (SCIENCE TIME JOURNAL, 2026)
Human language, in all its diversity, evolves and transforms through the interaction of communities, the passage of time, and the embeddedness of society in unique geographic, social, and historical circumstances. Within this dynamic process, dialects emerge, each carrying with it not merely differences in pronunciation or syntax, but a rich and multifaceted vocabulary that serves as a living repository of collective memory, cultural nuance, and social distinction. Both English and Uzbek, positioned in vastly different historical and sociopolitical contexts, display distinct as well as overlapping features in how dialect-specific words function sociolinguistically, shaping the life of their speakers and reflecting broader patterns of identity, belonging, and change.